1980
DOI: 10.1021/ac50058a013
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and cation-exchange selectivity of a perfluorosulfonate ion-exchange polymer

Abstract: may be possible to predict the extent of stacking of purines and pyrimidines in aqueous solutions from retention data. Futher work is now being carried out to examine these postulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 41 publications
3
118
0
Order By: Relevance
“…From experimental testing it is seen that this prediction counters the physical data that have been measured for the IPT. To address this discrepancy, the results of Yeager et al 41,42 were used to incorporate the temperature dependent variations in the diffusion coefficient d. These results demonstrated that the changes in d outweighed those of T, causing the high frequency impedance of the model to decrease with temperature, a result that agrees with experimental studies. The series of experimental studies conducted in this research also support and validate the proposed model.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…From experimental testing it is seen that this prediction counters the physical data that have been measured for the IPT. To address this discrepancy, the results of Yeager et al 41,42 were used to incorporate the temperature dependent variations in the diffusion coefficient d. These results demonstrated that the changes in d outweighed those of T, causing the high frequency impedance of the model to decrease with temperature, a result that agrees with experimental studies. The series of experimental studies conducted in this research also support and validate the proposed model.…”
Section: Discussionmentioning
confidence: 64%
“…These experiments indicate that the IPT's high frequency resistance actually decreases with a rise in temperature, contrary to the predictions of the model. To account for this discrepancy we revisit our model, incorporating interactions between the ambient temperature T and the diffusion coefficient d. Yeager et al 41,42 conducted several experimental studies that looked at the self-diffusion coefficient of Na + and Cs + through Nafion™ as a function of the ambient temperature. Yeager et al found that the diffusion coefficient had a strong dependence on temperature for each of the counterions considered.…”
Section: Temperature-tmentioning
confidence: 99%
See 2 more Smart Citations
“…Counterions with large hydration energies increase water uptake, as do low equivalent weights. It is interesting that up to 50% more water is taken up if the materials are boiled in water, compared to room temperature equilibration, and that this increased water is permanently retained after coo ling (15). Increases in water sorption are accompanied by decreases in elec trical resistance and tensile strength, as might be expectedQ2).…”
mentioning
confidence: 85%